The Еffectiveness of Learning German on Moodle - Marina Đ. Đukić Mirzayantz (University of Belgrade, Teacher Education Faculty, 2019)
This paper reports the results of the assessment of two distance elementary German courses, the first to be offered at Singidunum University in Serbia. The purpose of the assessment was to determine if there were significant differences in achievement between the students in the distance courses (experimental group) and those in the traditional courses (control group). The conclusion is that between those two groups, a statistically significant difference was shown only for testing listening comprehension, where the students attending traditional courses achieved better results. As for all other subtests (reading comprehension, writing and speaking skills), both groups were statistically equal. On the basis of a critical analysis of the model used for distance language learning, the most important directions for improvement of the existing practice were defined. This paper contributes to the ongoing efforts of the Ministry of Education, Science and Technological Development of the Republic of Serbia to expand the use of learning management systems in education institutions in Serbia.